Legal restrictions on portfolio holdings: Some empirical results - Jaroslava Hlouskova; Gabriel S. Lee (Institute for Advanced Studies (IHS), 2001)
This article investigates the sensitivity analysis of mean-variance portfolio holdings to changes in the upper bounds. The optimization problem studied in this paper is, thus, constrained by a restriction that no more than certain portion of wealth can be invested in any one security. Our empirical results show that for both risk tolerant as well as for risk averse investors, the performance and expected returns of mean-variance efficient portfolios under the legal restrictions are lower and the variance are higher than the corresponding ones without the restriction.
Keywords: C61; G11; 330; upper bound constraint; portfolio holdings; parametric quadratic programming; Portfolio-Management; Capital Asset Pricing Model; Wertpapieranalyse; Österreich